Why Do Intrauterine Exposure to Air Pollution and Cigarette Smoke Increase the Risk of Asthma? - Wang, Baoming; Chen, Hui; Chan, Yik Lung; Wang, Gang; Oliver, Brian G. (Frontiers in Cell and Developmental Biology, 2020)
The prevalence of childhood asthma is increasing worldwide and increased in-utero exposure to environmental toxicants may play a major role. As current asthma treatments are not curative, understanding the mechanisms underlying the aetiology of asthma will allow better preventative strategies to be developed. This review focuses on the current understanding of how in-utero exposure to environmental factors increases the risk of developing asthma in children. Epidemiological studies show that maternal smoking and particulate matter exposure during pregnancy are prominent risk factors for the development of childhood asthma. We discuss the changes in the developing foetus due to reduced oxygen and nutrient delivery affected by intrauterine environmental change. This leads to foetal underdevelopment and abnormal lung structure. Concurrently an altered immune response and aberrant epithelial and mesenchymal cellular function occur possibly due to epigenetic reprogramming. The sequelae of these early life events are airway remodelling, airway hyperresponsiveness, and inflammation, the hallmark features of asthma. In summary, the increased risk of childhood asthma due to maternal smoking and particular matter exposure involves multiple mechanisms, which make it challenging to reduce the risk of asthma, but can also help to develop personalised medicines.